PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA CV. WERY GROUP KOTA GUNUNGSITOLI - Laoli, Meri Eka Lestari; Harefa, Idarni; Laia, Otanius; Mendrofa, Yupiter (Jurnal Suluh Pendidikan, 2025)
This study aims to determine the effect of product quality and price on purchasing decisions at CV. Wery Group in Gunungsitoli City. Using quantitative methods, this study involves collecting data from consumers of CV. Wery Group. Based on the results of the study, it was found that product quality has a significant effect on purchasing decisions, as indicated by a significant value of <0.05 and a contribution of 83.3%. In addition, the results of the study also show that price has a significant effect on purchasing decisions with a significant value of <0.05 and a contribution of 71.4%. Furthermore, product quality and price together have a significant effect on purchasing decisions with a significant value of <0.05 and a contribution of 84.9%. These findings confirm that product quality, price, and service quality are key factors in improving purchasing decisions and consumer satisfaction at CV. Wery Group. Therefore, improving product quality, competitive pricing, and good service need to be a priority to strengthen consumer purchasing decisions in the future.